Tooth and consequences: Heterodonty and dental replacement in piranhas and pacus (Serrasalmidae). Issue 5 (26th August 2019) - Kolmann, Matthew A.; Cohen, Karly E.; Bemis, Katherine E.; Summers, Adam P.; Irish, Frances J.; Hernandez, L. Patricia
Abstract: Tooth replacement in piranhas is unusual: all teeth on one side of the head are lost as a unit, then replaced simultaneously. We used histology and microCT to examine tooth‐replacement modes across carnivorous piranhas and their herbivorous pacu cousins (Serrasalmidae) and then mapped replacement patterns onto a molecular phylogeny. Pacu teeth develop and are replaced in a manner like piranhas. For serrasalmids, unilateral tooth replacement is not an "all or nothing" phenomenon; we demonstrate that both sides of the jaws have developing tooth rows within them, albeit with one side more mineralized than the other. All serrasalmids (except one) share unilateral tooth replacement, so this is not an adaptation for carnivory. All serrasalmids have interlocking teeth; piranhas interdigitate lateral tooth cusps with adjacent teeth, forming a singular saw‐like blade, whereas lateral cusps in pacus clasp together. For serrasalmids to have an interlocking dentition, their teeth need to develop and erupt at the same time. We propose that interlocking mechanisms prevent tooth loss and ensure continued functionality of the feeding apparatus. Serrasalmid dentitions are ubiquitously heterodont, having incisiform and molariform dentitions reminiscent of mammals. Finally, we propose that simultaneous tooth replacement be considered as a synapomorphy for the family. Abstract : Tooth replacement in piranhas and pacus (Serrasalmidae) is unusual: All teeth on one side of the head are lost as a unit, then replaced simultaneously. We used histology and microCT to examine tooth‐replacement modes across carnivorous piranhas and their herbivorous pacu cousins. Unilateral tooth replacement arose in herbivorous pacu‐like ancestors, suggesting this tooth‐replacement mode is an exaptation for carnivory in piranha lineages. All serrasalmids have interlocking teeth; piranhas interdigitate lateral tooth cusps with adjacent teeth, forming a singular saw‐like blade, whereas lateral cusps in pacus clasp together. For serrasalmids to have an interlocking dentition, their teeth need to develop and erupt at the same time. RESEARCH HIGHLIGHTS: Piranhas and pacus lose all teeth on one side of their head at once. Teeth are also heterodont and lock together, therefore, needing to be replaced simultaneously. As this phenomenon arose in herbivorous pacus, it is exapted for carnivory in piranhas.